Ionic-liquid-based approaches to improve biopharmaceuticals downstream processing and formulation - Almeida, Catarina; Pedro, Augusto Q.; Tavares, Ana P. M.; Neves, Márcia C.; Freire, Mara G. (Frontiers in Bioengineering and Biotechnology, 2023)
The emergence of biopharmaceuticals, among them proteins, nucleic acids, peptides, and vaccines, contributed to significant advances in the medical field. In these, significant improvements were achieved in the prophylaxis and treatment of chronic and life-threatening diseases. Notwithstanding their clinical relevance, the manufacture of biopharmaceuticals involves a set of complex steps within the upstream and downstream processes, still coping with challenges that contribute to increase their cost. The downstream processing remains the main challenge and despite the efforts made in the last decades to improve the already used strategies, they still contribute to more than 80% of the total production cost of a biopharmaceutical. On the other hand, by being biological products, their formulation to keep their therapeutic performance (and long-term stability or preservation) is also a current challenge and a major bottleneck in the field. To surpass these drawbacks, while aiming the development of alternative cost-effective and sustainable purification platforms and the design of stable formulations for biopharmaceuticals, ionic-liquid-(IL)-based approaches have been investigated. Several works are currently available in the literature, showing the ability of IL-based systems to improve the downstream processing of biopharmaceuticals, by increasing their purity and recovery yield, and in the development of stable biopharmaceutical formulations. Given the relevance of these works, this manuscript reviews the most important progresses achieved in both fields. The work developed is critically discussed and complemented with a SWOT analysis. Future perspectives are finally provided.